Large Eddy Simulation of environmental impacts on mass transport in laboratory-scale vertical farm - Ashnani, Ali A.; Laitinen, Alpo; Karimkashi, Shervin; Vuorinen, Ville; Kotilainen, Titta; Näkkilä, Juha; Herranen, Pasi; Kaario, Ossi (Pergamon Press, 2026)
The impact of environmental factors on airflow and mass transport within a laboratory-scale vertical farm is investigated using Computational Fluid Dynamics. Large Eddy Simulation models complex airflow behaviour, while solving enthalpy and mass transport equations yields temperature, humidity, and CO2 concentration. The Eulerian-Lagrangian approach simulates the free-fall of water droplets in the dehumidifier-cooling system. Humidity and CO2 consumption/production by plants and utilities are modelled as volumetric sources/sinks. An experimental campaign is conducted to measure temperature, relative humidity, and CO2 above cultivation beds, validating the numerical setup with mean absolute errors of 0.8%, 2.2%, and 3.9%, respectively. Analysing the airflow shows that the free fall of droplets is the dominant mechanism driving airflow characteristics. We investigate the effects of wall confinement, number of lamps, and location of lamps on the mass transport. Curtains were used to divide each cultivation bed into three regions to assess the wall confinement effect. Results show the overall adverse effect of curtains on mass transport. In more detail, mass transport is enhanced when the curtains and streamlines are aligned parallel, whereas it is reduced when they are perpendicular. Increasing the number of operative lamps improves the uniformity of mass distribution on the upper cultivation beds due to a stronger positive buoyancy. Positioning lamp-induced buoyant flow within the droplet’s lateral momentum injection zone further enhances vertical mass transport. These findings highlight the impact of environmental factors on mass transport, offering insights for more efficient designs of indoor vertical farms.
Keywords: vertical farm; indoor plant factory; CEA; ventilation; environmental effect; CFD; LES